2012
DOI: 10.1515/forum-2012-0054
|View full text |Cite
|
Sign up to set email alerts
|

Locally finitely presented categories with no flat objects

Abstract: If X is a quasi-compact and quasi-separated scheme, the category Qcoh(X) of quasi-coherent sheaves on X is locally finitely presented. Therefore categorical flat quasi-coherent sheaves in the sense of [30] naturally arise. But there is also the standard definition of flatness in Qcoh(X) from the stalks. So it makes sense to wonder the relationship (if any) between these two notions. In this paper we show that there are plenty of locally finitely presented categories having no other categorical flats than the z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The converse is not true, in general, for non-affine schemes. This is one of the main results in [8] ( [8, theorem 4.4]). Section 4 of the paper is devoted to showing that pure injective envelopes do exist with respect to both notions of purity.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…The converse is not true, in general, for non-affine schemes. This is one of the main results in [8] ( [8, theorem 4.4]). Section 4 of the paper is devoted to showing that pure injective envelopes do exist with respect to both notions of purity.…”
Section: Introductionmentioning
confidence: 72%
“…, we obtain the commutative diagram with exact rows: it was shown that Flat fp = 0 for the case in which X = P n (R). In general there is a large class of projective schemes X such that Flat fp = 0 in Qcoh(X) (see [8,Theorem 4.4]).…”
Section: Definition 310mentioning
confidence: 99%
See 1 more Smart Citation
“…If the two notions of purity were the same then it is not hard to see [EE016,corollary 3•12] that the categorical flats in Qcoh(X ) are precisely the usual flats in Qcoh(X ) (that is, flatness in terms of the stalks). But this is not the case; for instance for projective spaces, it was shown in [ES15,corollary 4•6] that the only categorical flat sheaf is the zero sheaf in this case.…”
Section: Introductionmentioning
confidence: 99%
“…The class of flat and fp-flat quasi coherent sheaves are denoted by Flat ⊗ and Flat f p respectively. It is proved in [5, section 3] and in [7] that Pure f p ⊆ Pure ⊗ and Flat f p ⊆ Flat ⊗ .…”
Section: Introductionmentioning
confidence: 99%